Producing 3D Biomimetic Nanomaterials for Musculoskeletal System Regeneration - Casanellas, Ignasi; García-Lizarribar, Andrea; Lagunas, Anna; Samitier, Josep (Frontiers in Bioengineering and Biotechnology, 2018)
The human musculoskeletal system is comprised mainly of connective tissues such as cartilage, tendon, ligaments, skeletal muscle and skeletal bone. These tissues support the structure of the body, hold and protect the organs, and are responsible of movement. Since it is subjected to continuous strain, the musculoskeletal system is prone to injury by excessive loading forces or aging, whereas currently available treatments are usually invasive and not always effective. Most of the musculoskeletal injuries require surgical intervention facing a limited post-surgery tissue regeneration, especially for widespread lesions. Therefore, many tissue engineering approaches have been developed tackling musculoskeletal tissue regeneration. Materials are designed to meet the chemical and mechanical requirements of the native tissue three-dimensional (3D) environment, thus facilitating implant integration while providing a good reabsorption rate. With biological systems operating at the nanoscale, nanoengineered materials have been developed to support and promote regeneration at the interprotein communication level. Such materials call for a great precision and architectural control in the production process fostering the development of new fabrication techniques. In this mini review, we would like to summarize the most recent advances in 3D nanoengineered biomaterials for musculoskeletal tissue regeneration, with especial emphasis on the different techniques used to produce them.